Effects of Ring Flange Type, Traveler Weight and Coating on Cotton Yarn Properties - (:unkn) unknown (Nova Science Publishers, Inc., 2014)
Ring spinning is the most important and effective staple yarn production process. A ring spinning machine consists of a variety of parts of which rings and travellers are the dominant elements. This experimental study has highlighted that the ring flanges and the ring travellers have an effect on the properties of 100% cotton yarn. The interaction between the yarn quality and the spinning elements has been analysed. Ne 40/1 cotton yarns were produced by using both flange 1 and flange 2 rings, half round (dr) and flat (f) profile of ring travellers with four different traveller masses and five different traveller coatings. 80 copses of yarn were produced by using different process combinations. The yarn properties were tested in terms of yarn count, yarn twist, irregularity, yarn hairiness, strength, elongation, spinning tension and balloon angle. As a result, yarn twist and count decreased with increasing spinning tension. Spinning tension in Flange 1 was greater than spinning tension in Flange 2. Increasing the spinning tension improved the following yarn properties; yarn hairiness and yarn twist. The properties of the yarns produced with Flange 2 show better properties than the yarns produced with Flange 1. Increase in ring traveller weight also improved the yarn properties. © 2014 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Cotton yarn; Flange; Hairiness; Ring spinning; Traveller; Yarn irregularity